Factors Related To The Incidence Of Stunting In Toddlers - Tiotor, Frisye; Arnoli, Andi; Syam, Ilham (Bantayang Omni Cendekia, 2024)
Background: Stunting is a condition of failure to thrive in children caused by chronic malnutrition during the growth period. Jeneponto Regency is the region with the highest prevalence of stunting toddlers in South Sulawesi in 2022, reaching 39.8%. This figure is up 1.9 points from the prevalence of stunting toddlers in the area in 2021 of 37.9%, so the problem of stunting is still a health problem in Jeneponto. Binamu Health Center is one of 18 Health Centers in Jeneponto Regency. The results of the initial data survey from January until April 2023 found that 233 children suffering from stunting were stunted. Objective: This study aims to determine the factors associated with the incidence of stunting in toddlers. Methods: This research is quantitative research with cross-sectional study method. The sample in this study was toddlers totaling 278 people. The sampling technique is purposive sampling. This study used questionnaires as a data collection instrument. Results: The results of the study found that exclusive breastfeeding obtained Chi-Square test results obtained P-value = 0.000 (P < α = 0.05), which means there is a relationship between exclusive breastfeeding and stunting incidence, maternal education with stunting incidence obtained chi-square test results obtained p-value = 0.548 (p < α = 0.05) which means there is no significant relationship between maternal education and stunting incidence and BBLR obtained chi-square test results p-value = 0.391 ( P < α = 0.05), which means there is no relationship between low birth weight and the incidence of stunting in toddlers. Conclusion: The conclusion of this study is that there is a relationship between exclusive breastfeeding and the incidence of stunting, while maternal education and low birth weight are not related to the incidence of stunting.